An 1860 English-Hopi Vocabulary Written in the Deseret Alphabet - Beesley, Kenneth R., 1954-; Elzinga, Dirk (Book collections on Project MUSE., 2015)
Reproduces the dictionary compiled by two Mormon missionaries to the Hopi and written in a non-Roman phonemic alphabet that Brigham Young was promoting. Also includes a discussion of the provenance and background of the book, the Hopi language, and the Mormon mission; identifies Hopi words in modern dictionaries; and transcribes words from the Deseret Alphabet into the International Phonetic Alphabet.